2014
DOI: 10.1007/s11695-014-1415-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleeve Gastrectomy on Thyroid Hormone Levels

Abstract: This is the first study to evaluate changes in thyroid hormone levels following LSG for morbid obesity. TSH decrease and steady levels of FT4 are expected following LSG. These findings are comparable to reported changes following LRYGB. TSH decrease was not associated with EWL. Further studies are required to elucidate the exact mechanism of this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 25 publications
4
32
1
Order By: Relevance
“…The mechanism and the clinical implications of this alteration remains uncertain. Furthermore, the effect of bariatric surgery on postoperative thyroid function remains incompletely understood with previous studies showing contradictory results regarding the variation of TSH after bariatric surgery and the relation of TSH variation with postoperative weight loss [12][13][14][15][16][17][18][19]. Therefore, our aim was to evaluate the effect of weight loss after bariatric surgery on TSH variation in patients with morbid obesity and normal thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism and the clinical implications of this alteration remains uncertain. Furthermore, the effect of bariatric surgery on postoperative thyroid function remains incompletely understood with previous studies showing contradictory results regarding the variation of TSH after bariatric surgery and the relation of TSH variation with postoperative weight loss [12][13][14][15][16][17][18][19]. Therefore, our aim was to evaluate the effect of weight loss after bariatric surgery on TSH variation in patients with morbid obesity and normal thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…Abu-Ghanem et al [15] found significant decrease in TSH with no change in FT4 in patients after LSG compared to results seen after LRYGB by Moulin et al and Chikunguwoet al in euthyroid patients [8,9].…”
Section: Discussionmentioning
confidence: 85%
“…The exact mechanism of improvement of thyroid dysfunction status after bariatric surgery related not only to weight loss but also to the hormonal change after LSG, LRYGB as hypothesized by different studies in which the level of TSH reduction was not directly correlated to the EWL [4,8,15].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Following weight loss, fT3 levels decreased and fT4 increased, with no changes in serum TSH [11]. The mean TSH levels declined from 2.45 mU/L to 1.82 mU/L, but there was no change in fT4 -levels within 6-12 months after weight loss, as determined by sleeve gastrectomy of 38 morbidly obese subjects [12].…”
Section: Introductionmentioning
confidence: 89%